Effects of the extrusion conditions, the addition of oil and the food matrix on the physical and sensory characteristics of pre-extrusion flavored products - Flôres, Isadora Giacomini [UNESP]; Salles, Christian; Conti, Ana Carolina [UNESP] (Springer Nature, 2024)
Thermoplastic extrusion is important in processing a wide variety of food products. In this paper, the effects of different extrusion conditions, addition of vegetable oil and the food matrix itself on the physical and sensory characteristics of corn snacks and meat analogs were evaluated. Cysteine and butyric acid (cheese aroma precursors) and thiamine (a meat aroma precursor) were added to corn grits and soy protein concentrate, respectively, before extrusion. For each matrix, three combinations of moistures of the raw material and extrusion temperatures were used and, after extrusion, vegetable oil was added to one portion of each product and not to another one. The extrusion conditions and the addition of oil affected the physical properties and sensory characteristics of corn snacks more while they had less influence on the properties of the meat analogs. There were similar correlations between the physical and sensory variables, independent of the food matrix used. The sensory acceptance stood out for samples from intermediate and less severe extrusion conditions and with added oil, showing that these factors have an impact on the physical properties and sensory characteristics, with little effect from the food matrix.
Keywords: Aroma precursor; Meat analogs; Snacks; Thermoplastic extrusion